P2 / O3 double-phase composite material, preparation method and application thereof, and sodium ion battery
By preparing P2/O3 biphase composite materials, the problem of poor circulation stability of the existing sodium ion battery positive electrode materials is solved, high discharge capacity and good cycle stability are achieved, electrochemical performance is improved and cost is reduced.
Patent Information
- Application Number
- CN202510272377.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-10
AI Technical Summary
The existing P2/O3 composite phase sodium ion battery positive electrode material has poor circulation stability and is difficult to meet the needs of high capacity and good circulation performance.
By preparing a P2/O3 biphase composite material, the composition of the P2 phase is NaxMnO2 (0.45≤x≤0.7) and the composition of the O3 phase is NayNiaCubFecMndO2 (0.75≤y≤1, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6), and the composite material is synthesized through a specific calcination step to enhance its cycle stability.
The high discharge capacity and good cycle stability of P2/O3 biphase composites in sodium ion batteries are achieved, which improves electrochemical performance and reduces costs.
Smart Images

Figure CN119764431A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a P2 / O3 two-phase composite material, a preparation method and application thereof, and a sodium ion battery. Background Art
[0002] Sodium-ion batteries have the advantages of abundant sodium resources, low cost, and similar charging and discharging mechanisms to lithium-ion batteries. They are a potential alternative to lithium-ion batteries.
[0003] In sodium-ion batteries, cathode materials are an important factor that restricts the performance indicators of sodium-ion batteries, such as capacity, energy density and safety. Among the many cathode materials for sodium-ion batteries, layered cathode materials have attracted widespread attention due to their good electrochemical reversibility, high theoretical capacity and easy synthesis.
[0004] According to the different coordination environments of sodium ions, layered positive electrode materials are mainly divided into P2 type and O3 type. Among them, P2 type is a sodium-deficient compound with open prismatic channels, which can realize rapid ion extraction and insertion, and has good structural stability, but its capacity is relatively low; while O3 type has the advantage of high specific capacity, but poor structural stability, resulting in poor cycle stability. Therefore, the current research direction in this field is to synthesize a new type of sodium ion battery positive electrode material by synthesizing a P2 / O3 composite phase, combining the advantages of the two phases of P2 and O3, and then synthesizing a new type of sodium ion battery positive electrode material. However, the new sodium ion battery positive electrode materials with P2 / O3 composite phases currently developed often have poor cycle stability. Summary of the invention
[0005] The purpose of the present invention is to provide a P2 / O3 dual-phase composite material, a preparation method and application thereof, and a sodium ion battery. The P2 / O3 dual-phase composite material provided by the present invention has good cycle stability on the basis of having a high discharge capacity.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a P2 / O3 dual-phase composite material, comprising a P2 phase and an O3 phase; The composition of the P2 phase is Na x MnO2, where 0.45≤x≤0.7; The composition of the O3 phase is Na y Ni a Cu b Fe c Mn d O2, where 0.75≤y≤1, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6; a, b and c are not 0 at the same time, a+b+c+d=1.
[0007] Preferably, the total proportion of the P2 phase and the O3 phase in the P2 / O3 dual-phase composite material is 100%.
[0008] Preferably, the phase ratio of the P2 phase to the O3 phase is 1:1, 2:1, 3:1 or 4:1.
[0009] Preferably, the space group of the P2 phase is P63 / mmc; and the space group of the O3 phase is R-3m.
[0010] The present invention provides a method for preparing the P2 / O3 dual-phase composite material described in the above technical solution, comprising the following steps: The P2 / O3 dual-phase composite material is prepared according to the composition of the P2 / O3 dual-phase composite material.
[0011] Preferably, the preparation method of the P2 / O3 dual-phase composite material comprises the following steps: Provide a precursor; the precursor is composed of Ni a Cu b Fe c Mn d (OH)2, the molar ratio of Ni, Cu, Fe and Mn in the precursor is the same as the molar ratio of Ni, Cu, Fe and Mn in the O3 phase; The precursor is mixed with a sodium source and subjected to a first calcination to obtain a first material; The first material is mixed with a manganese source and subjected to a second calcination to obtain the P2 / O3 dual-phase composite material.
[0012] Preferably, the sodium source includes at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide; the manganese source includes at least one of manganese acetate, manganese carbonate, manganese nitrate, manganese dioxide and manganese trioxide.
[0013] Preferably, the temperature of the first calcination is 300-650°C, the holding time is 1-5h, and the heating rate to the temperature of the first calcination is 1-5°C / min; The temperature of the second calcination is 700-950° C., the holding time is 8-24 hours, and the heating rate to the temperature of the second calcination is 1-5° C. / min.
[0014] The present invention provides an application of a P2 / O3 two-phase composite material in a sodium ion battery, wherein the P2 / O3 two-phase composite material is used as a positive electrode material of the sodium ion battery; the P2 / O3 two-phase composite material is the P2 / O3 two-phase composite material described in the above technical scheme or the P2 / O3 two-phase composite material obtained by the preparation method described in the above technical scheme.
[0015] The present invention provides a sodium ion battery, wherein the positive electrode material of the sodium ion battery is the P2 / O3 two-phase composite material described in the above technical solution or the P2 / O3 two-phase composite material obtained by the preparation method described in the above technical solution.
[0016] The present invention provides a P2 / O3 two-phase composite material, comprising a P2 phase and an O3 phase; the composition of the P2 phase is Na x MnO2, wherein 0.45≤x≤0.7; the composition of the O3 phase is Na y Ni a Cu b Fe c Mn d O2, wherein 0.75≤y≤1, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6; a, b and c are not 0 at the same time, a+b+c+d=1. The present invention realizes the construction of O3 type structure by introducing sodium ions into P2 / O3 two-phase composite material; at the same time, the present invention also introduces manganese ions into P2 / O3 two-phase composite material, and manganese ions are extremely electronegative, which can enhance the repulsion between positive and negative ions, thereby gradually forming a P2 type structure with a larger interlayer spacing, and the content of introduced manganese ions is more, and the repulsion between positive and negative ions in the system is stronger, so more P2 type structures can be formed, which promotes the improvement of cycle performance. Therefore, the P2 / O3 two-phase composite material provided by the present invention has a higher discharge capacity and good cycle stability.
[0017] The present invention provides a method for preparing the P2 / O3 two-phase composite material described in the above technical solution, and a specific ratio of P2 / O3 symbiotic composite phases can be selected and synthesized according to the required electrochemical performance. Moreover, the preparation method provided by the present invention is simple to operate, the source of raw materials is abundant, and the obtained P2 / O3 two-phase composite material has good electrochemical properties. When the P2 / O3 two-phase composite material prepared by the present invention is applied to a sodium ion battery as a positive electrode material, the ratio of the composite phase is controllable, the synthesis method is simple, and the cost can be effectively reduced on the basis of improving the electrochemical performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0019] Figure 1 XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 1; Figure 2This is a SEM image of the P2 / O3 dual-phase composite material prepared in Example 1; Figure 3 XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 2; Figure 4 This is a SEM image of the P2 / O3 dual-phase composite material prepared in Example 2; Figure 5 XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 3; Figure 6 This is a SEM image of the P2 / O3 dual-phase composite material prepared in Example 3; Figure 7 XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 4; Figure 8 This is a SEM image of the P2 / O3 dual-phase composite material prepared in Example 4; Fig. 9 XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 5; Fig.10 This is a SEM image of the P2 / O3 dual-phase composite material prepared in Example 5; Fig.11 XRD pattern of the P2 / O3 dual-phase composite material prepared in Comparative Example 1; Fig.12 This is the SEM image of the P2 / O3 dual-phase composite material prepared in Comparative Example 1; Fig.13 This is a phase ratio diagram of different proportions of the P2 / O3 two-phase composite material prepared in the experimental example. DETAILED DESCRIPTION
[0020] The present invention provides a P2 / O3 dual-phase composite material, comprising a P2 phase and an O3 phase; The composition of the P2 phase is Na x MnO2, where 0.45≤x≤0.7; The composition of the O3 phase is Na y Ni a Cu b Fe c Mn d O2, where 0.75≤y≤1, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6; a, b and c are not 0 at the same time, a+b+c+d=1.
[0021] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0022] In the present invention, the total proportion of the P2 phase and the O3 phase in the P2 / O3 dual-phase composite material may be 100%. In the present invention, the phase ratio of the P2 phase to the O3 phase may be 1:1, 2:1, 3:1 or 4:1.
[0023] In the present invention, the composition of the P2 phase is Na x MnO2. In the present invention, Na x In MnO2, the value of x is 0.45≤x≤0.7; in a specific embodiment of the present invention, the value of x can be 0.55, 0.65 or 0.7. In the present invention, the space group of the P2 phase can be P63 / mmc. In the present invention, the role of the P2 phase is to enhance the cyclic stability of the obtained dual-phase composite material.
[0024] In the present invention, the composition of the O3 phase is Na y Ni a Cu b Fe c Mn d O2. In the present invention, Na y Ni a Cu b Fe c Mn d In O2, the value of x is 0.75≤y≤1; in a specific embodiment of the present invention, the value of x can be 0.75, 0.8 or 0.85. y Ni a Cu b Fe c Mn d In O2, the value of a is 0≤a≤0.35; in a specific embodiment of the present invention, the value of a can be 0.11, 0.23 or 0.33. y Ni a Cu b Fe c Mn d In O2, the value of b is 0≤b≤0.35; in a specific embodiment of the present invention, the value of b can be 0.11, 0.22 or 0.3. y Ni a Cu b Fe c Mn d In O2, the value of c is 0≤c≤0.35; in a specific embodiment of the present invention, the value of c can be 0.11, 0.22 or 0.33. y Ni a Cu b Fe cMn d In O2, the value of d is 0.1≤d≤0.6; in a specific embodiment of the present invention, the value of d can be 0.33, 0.45 or 0.5. In the present invention, the space group of the O3 phase can be R-3m. In the present invention, the role of the O3 phase is to enhance the discharge capacity of the obtained dual-phase composite material.
[0025] The present invention also provides a method for preparing the P2 / O3 dual-phase composite material described in the above technical solution, comprising the following steps: The P2 / O3 dual-phase composite material is prepared according to the composition of the P2 / O3 dual-phase composite material.
[0026] In the present invention, the preparation method of the P2 / O3 dual-phase composite material may include the following steps: Provide a precursor; the precursor is composed of Ni a Cu b Fe c Mn d (OH)2, the molar ratio of Ni, Cu, Fe and Mn in the precursor is the same as the molar ratio of Ni, Cu, Fe and Mn in the O3 phase; The precursor is mixed with a sodium source and subjected to a first calcination to obtain a first material; The first material is mixed with a manganese source and subjected to a second calcination to obtain the P2 / O3 dual-phase composite material.
[0027] In the present invention, the preparation method of the precursor refers to patent document CN116375111A.
[0028] In the present invention, the sodium source may include at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide; in a specific embodiment of the present invention, the sodium source may be sodium carbonate, sodium bicarbonate or sodium hydroxide.
[0029] In the present invention, the manganese source may include at least one of manganese acetate, manganese carbonate, manganese nitrate, manganese dioxide and manganese trioxide. In a specific embodiment of the present invention, the manganese source may be manganese acetate, manganese carbonate, manganese nitrate, manganese dioxide or manganese trioxide.
[0030] In the present invention, the temperature of the first roasting can be 300-650°C, the holding time can be 1-5h, and the heating rate to the temperature of the first roasting can be 1-5°C / min. In a specific embodiment of the present invention, the temperature of the first roasting is 300°C, 400°C, 500°C, 600°C or 650°C; the holding time of the first roasting is 1h, 2h, 3h, 4h or 5h; the heating rate to the temperature of the first roasting is 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.
[0031] In the present invention, the temperature of the second roasting can be 700-950°C, the holding time can be 8-24h, and the heating rate to the temperature of the second roasting can be 1-5°C / min. In a specific embodiment of the present invention, the temperature of the second roasting is 700°C, 750°C, 800°C, 850°C, 900°C or 950°C; the holding time of the second roasting is 8h, 12h, 16h, 20h or 24h; the heating rate to the temperature of the second roasting is 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.
[0032] The present invention also provides an application of a P2 / O3 two-phase composite material in a sodium ion battery, wherein the P2 / O3 two-phase composite material is used as a positive electrode material of the sodium ion battery; the P2 / O3 two-phase composite material is the P2 / O3 two-phase composite material described in the above technical scheme or the P2 / O3 two-phase composite material obtained by the preparation method described in the above technical scheme.
[0033] The present invention also provides a sodium ion battery, wherein the positive electrode material of the sodium ion battery is the P2 / O3 two-phase composite material described in the above technical solution or the P2 / O3 two-phase composite material obtained by the preparation method described in the above technical solution. In the present invention, the sodium ion battery may also include a negative electrode material and an electrolyte. In the present invention, the negative electrode material of the sodium ion battery may be composed of sodium sheets or hard carbon. In the present invention, the electrolyte of the sodium ion battery may be a NaPF6 solution or a NaClO4 solution. In the present invention, the sodium ion battery may also include a diaphragm; the diaphragm may be composed of glass fiber. In a specific embodiment of the present invention, the sodium ion battery is a CR2032 button half-cell, comprising a positive electrode material, a negative electrode material, an electrolyte and a separator; the positive electrode material is composed of a P2 / O3 two-phase composite material, conductive carbon black, vinylidene fluoride and N-methylpyrrolidone, and the mass ratio of the P2 / O3 two-phase composite material, conductive carbon black and vinylidene fluoride is 9:0.5:0.5; the negative electrode material is a sodium sheet; the electrolyte is composed of NaClO4 / polycarbonate (i.e., a polycarbonate solution of NaClO4), ethylene carbonate and dimethyl carbonate, and the volume ratio of NaClO4 / polycarbonate, ethylene carbonate and dimethyl carbonate is 1:1:1; the separator is composed of glass fiber. The present invention can assemble the positive electrode material, the negative electrode material, the electrolyte and the separator in an argon atmosphere to obtain a sodium ion battery.
[0034] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1 This embodiment provides a method for preparing a P2 / O3 dual-phase composite material, wherein the P2 / O3 dual-phase composite material is composed of a P2 phase and an O3 phase, wherein the composition of the P2 phase is NaMnO2, and the space group is P63 / mmc; the composition of the O3 phase is NaNi 0.22 Cu 0.1 Fe 0.32 Mn 0.36 O2, space group is R-3m.
[0036] The NaNi 0.22 Cu 0.1 Fe 0.32 Mn 0.36 Precursor of (OH)2.
[0037] Sodium carbonate and the precursor are weighed according to the above molar ratio, and the weighed sodium carbonate, the precursor and ethanol are put into a grinding mortar and mixed evenly. After drying, the obtained material is put into a tube furnace, and the temperature is uniformly increased to 600° C. at a rate of 3° C. / min, and then kept at 600° C. for 2 hours in an air atmosphere. After the end, the obtained material is cooled to room temperature to obtain the first material.
[0038] 2% manganese acetate was weighed according to the molar ratio, and the weighed manganese acetate, ethanol and the first material were put into a grinding mortar and mixed evenly. After drying, the obtained material was put into a tube furnace, and the temperature was uniformly increased to 800°C at a rate of 3°C / min, and then kept at 850°C for 10 hours in an air atmosphere. After the end, the obtained material was naturally cooled to room temperature in air to obtain a P2 / O3 dual-phase composite material.
[0039] The XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the P2 / O3 dual-phase composite material obtained in Example 1 contains P2 phase and O3 phase.
[0040] The SEM image of the P2 / O3 dual-phase composite material prepared in Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the P2 / O3 dual-phase composite material obtained in Example 1 is a microspherical particle composed of flaky particles, and the flaky structure is not obvious.
[0041] Example 2 A P2 / O3 dual-phase composite material was prepared according to the conditions of Example 1, except that the molar amount of manganese acetate was replaced from 2% to 5%.
[0042] The XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 2 is as follows: Figure 3 As shown by Figure 3 It can be seen that the P2 / O3 dual-phase composite material prepared in Example 2 contains P2 phase and O3 phase.
[0043] The SEM image of the P2 / O3 dual-phase composite material prepared in Example 2 is as follows: Figure 4 As shown by Figure 4 It can be seen that the P2 / O3 dual-phase composite material prepared in Example 2 is a microspherical particle composed of flaky particles, the flaky structure is not obvious, and some fine particles begin to appear around it.
[0044] Example 3 A P2 / O3 dual-phase composite material was prepared according to the conditions of Example 1, except that the molar amount of manganese acetate was replaced from 2% to 10%.
[0045] The XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 3 is as follows: Figure 5 As shown by Figure 5 It can be seen that the P2 / O3 dual-phase composite material prepared in Example 3 contains P2 phase and O3 phase.
[0046] The SEM image of the P2 / O3 dual-phase composite material prepared in Example 3 is as follows: Figure 6 As shown by Figure 6 It can be seen that the P2 / O3 dual-phase composite material prepared in Example 3 is a microspherical particle composed of flaky particles, the flaky structure is not obvious, and some small particles around it are gradually increasing.
[0047] Example 4 A P2 / O3 dual-phase composite material was prepared according to the conditions of Example 1, except that the molar amount of manganese acetate was replaced from 2% to 15%.
[0048] The XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 4 is as follows: Figure 7 As shown by Figure 7 It can be seen that the P2 / O3 dual-phase composite material prepared in Example 4 contains P2 phase and O3 phase.
[0049] The SEM image of the P2 / O3 dual-phase composite material prepared in Example 4 is as follows: Figure 8 As shown by Figure 8 It can be seen that the P2 / O3 dual-phase composite material prepared in Example 4 is a microspherical particle composed of flaky particles, the flaky structure is not obvious, and there are some fine particles around it.
[0050] Example 5 A P2 / O3 dual-phase composite material was prepared according to the conditions of Example 1, except that the molar amount of manganese acetate was replaced from 2% to 20%.
[0051] The XRD pattern of the P2 / O3 dual-phase composite material prepared in Example 5 is as follows: Fig. 9 As shown by Fig. 9 It can be seen that the P2 / O3 dual-phase composite material prepared in Example 5 contains P2 phase and O3 phase.
[0052] The SEM image of the P2 / O3 dual-phase composite material prepared in Example 5 is as follows: Fig.10 As shown by Fig.10 It can be seen that the P2 / O3 dual-phase composite material prepared in Example 5 is a microspherical particle composed of flaky particles, the flaky structure is not obvious, and there are some fine particles around it.
[0053] It can be seen from Examples 1 to 5 that as the Mn content in the P2 / O3 dual-phase composite material increases, the particle size of the primary particles in the obtained P2 / O3 dual-phase composite material gradually decreases.
[0054] Comparative Example 1 An electrode material was prepared according to the conditions of Example 1, except that no manganese source was added.
[0055] The XRD pattern of the electrode material prepared in Comparative Example 1 is as follows: Fig.11 As shown by Fig.11 It can be seen that the electrode material prepared in Comparative Example 1 only contains O3 phase.
[0056] The SEM image of the electrode material prepared in Comparative Example 1 is as follows Fig.12 As shown by Fig.12 It can be seen that the electrode material prepared in Comparative Example 1 is a microspherical particle composed of flaky particles, the flaky structure is relatively clear, and the particle size of the primary particles is relatively large.
[0057] Test Example 1 XRD test analysis The P2 / O3 dual-phase composite materials obtained in Examples 1 to 5 and the electrode material obtained in Comparative Example 1 were subjected to XRD test analysis. The test results are as follows: Fig.13 shown.
[0058] Depend on Fig.13 It can be seen that the P2 / O3 dual-phase composite materials obtained in Examples 1 to 5 all have a P2 / O3 dual-phase structure. By adjusting the element content in the P2 / O3 dual-phase composite material, the ratio of the P2 and O3 dual-phases is also changed; while the electrode material obtained in Comparative Example 1 without any element change is an O3 phase structure. Test Example 2 Electrochemical Performance Test (1) Under an inert atmosphere, the P2 / O3 dual-phase composite material obtained in Example 1, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) in a mass ratio of 9:0.5:0.5 for slurry preparation, and the obtained slurry was coated on aluminum foil, vacuum dried, and cut into composite materials with a diameter of 12 mm (loading of about 5-10 mg / cm 2 ).
[0059] (2) 1 mol / L NaClO4 / polycarbonate (PC), ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1 to obtain an electrolyte, glass fiber was used as a separator, sodium sheet was used as a negative electrode material, and the composite material obtained in step (1) was used as a positive electrode material, and assembled into a CR2032 button half-cell in an argon glove box.
[0060] (3) Charge and discharge test: The charge and discharge voltage range of the CR2032 button half-cell is 2.0~4.1V. Before the cycle test, the CR2032 button half-cell is activated twice with a smaller current density of 15mA / g (0.1C), and then cycled in the voltage range of 2.0~4.1V at a rate of 1C. All electrochemical performance tests are carried out at room temperature.
[0061] (4) The P2 / O3 dual-phase composite material obtained in Example 1 was replaced by the P2 / O3 dual-phase composite material obtained in Examples 2 to 5 and the electrode material obtained in Comparative Example 1, respectively, and steps (1), (2) and (3) were repeated to complete the electrochemical performance test of CR2032 button half-cells composed of different positive electrode materials. The results are shown in Table 1.
[0062] Table 1 Electrochemical performance of CR2032 button half-cells composed of different cathode materials
[0063] It can be seen from Table 1 that the initial capacity of the CR2032 button half-cell composed of the P2 / O3 dual-phase composite structure is slightly lower than that of the O3 single-phase structure material, and the decrease is within an acceptable range, but the cycle performance of the CR2032 button half-cell is greatly improved; when the P2 / O3 dual-phase ratio is 1:1, the electrical performance of the CR2032 button half-cell composed of the P2 / O3 dual-phase composite material reaches the best.
[0064] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A P2 / O3 dual-phase composite material, characterized in that: Includes P2 phase and O3 phase; The composition of the P2 phase is Na x MnO2, where 0.45≤x≤0.7; The composition of the O3 phase is Na y Ni a Cu b Fe c Mn d O2, where 0.75≤y≤1, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6; a, b and c are not 0 at the same time, a+b+c+d=1.
2. The P2 / O3 dual-phase composite material according to claim 1, characterized in that: The total proportion of the P2 phase and the O3 phase in the P2 / O3 dual-phase composite material is 100%.
3. The P2 / O3 dual-phase composite material according to claim 2, characterized in that: The phase ratio of the P2 phase to the O3 phase is 1:1, 2:1, 3:1 or 4:
1.
4. The P2 / O3 dual-phase composite material according to claim 1, characterized in that: The space group of the P2 phase is P63 / mmc; the space group of the O3 phase is R-3m.
5. The method for preparing the P2 / O3 dual-phase composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The P2 / O3 dual-phase composite material is prepared according to the composition of the P2 / O3 dual-phase composite material.
6. The preparation method according to claim 5, characterized in that: The preparation method of the P2 / O3 dual-phase composite material comprises the following steps: Provide a precursor; the precursor is composed of Ni a Cu b Fe c Mn d (OH)2, the molar ratio of Ni, Cu, Fe and Mn in the precursor is the same as the molar ratio of Ni, Cu, Fe and Mn in the O3 phase; The precursor is mixed with a sodium source and subjected to a first calcination to obtain a first material; The first material is mixed with a manganese source and subjected to a second calcination to obtain the P2 / O3 dual-phase composite material.
7. The preparation method according to claim 6, characterized in that: The sodium source includes at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide; the manganese source includes at least one of manganese acetate, manganese carbonate, manganese nitrate, manganese dioxide and manganese trioxide.
8. The preparation method according to claim 6, characterized in that: The temperature of the first calcination is 300-650°C, the holding time is 1-5h, and the heating rate to the temperature of the first calcination is 1-5°C / min; The temperature of the second calcination is 700-950° C., the holding time is 8-24 hours, and the heating rate to the temperature of the second calcination is 1-5° C. / min.
9. Application of a P2 / O3 dual-phase composite material in a sodium ion battery, characterized in that: The P2 / O3 two-phase composite material is used as a positive electrode material for a sodium ion battery; the P2 / O3 two-phase composite material is the P2 / O3 two-phase composite material described in any one of claims 1 to 4 or the P2 / O3 two-phase composite material obtained by the preparation method described in any one of claims 5 to 8.
10. A sodium ion battery, characterized in that: The positive electrode material of the sodium ion battery is the P2 / O3 dual-phase composite material described in any one of claims 1 to 4 or the P2 / O3 dual-phase composite material obtained by the preparation method described in any one of claims 5 to 8.
Citation Information
Patent Citations
Layered oxide with mixed phase structure as well as preparation method and application of layered oxide
CN116314659A
Coated sodium-based layered oxide composite material, preparation method thereof and sodium ion battery
CN116826014A
Sodium-ion battery positive electrode material with low-nickel shell structure and preparation method of sodium-ion battery positive electrode material
CN117219772A
Core-shell structure sodium ion battery positive electrode material and preparation method and application thereof
CN117878284A
Preparation method of multi-cation co-doped O3-NaNi1 / 3Fe1 / 3Mn1 / 3O2 layered sodium ion battery positive electrode material
CN119230816A